2006
DOI: 10.1111/j.1442-2042.2006.01584.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐titration of vardenafil dose from 10 mg to 20 mg improved erectile function in men with spinal cord injury

Abstract: Aim: Vardenafil is a highly selective phosphodiesterase type-5 inhibitor for the treatment of erectile dysfunction (ED). Efficacy of vardenafil has been demonstrated in various ED populations, but that in Japanese patients with spinal cord injury (SCI) has not been assessed. Methods:This was an open-label, multicenter, flexible dose, 12-week study in patients with ED due to SCI. Following a 4-week observation period, patients received vardenafil 10 mg for 4 weeks, and based on efficacy, tolerability and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…18 PDE5 inhibitors have also changed the treatment of ED in SCI patients, becoming the preferred treatment in subjects with SCI since the introduction of sildenafil because of their ease of use and effectiveness. [19][20][21] Nevertheless the role of PDE5 inhibitors to treat ED caused by SCI has not been well assessed. It is still challenging to identify the efficacy and safety of PDE5 inhibitors in SCI patients suffering from ED.…”
Section: Introductionmentioning
confidence: 99%
“…18 PDE5 inhibitors have also changed the treatment of ED in SCI patients, becoming the preferred treatment in subjects with SCI since the introduction of sildenafil because of their ease of use and effectiveness. [19][20][21] Nevertheless the role of PDE5 inhibitors to treat ED caused by SCI has not been well assessed. It is still challenging to identify the efficacy and safety of PDE5 inhibitors in SCI patients suffering from ED.…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence suggests that PDE-5 inhibitors are a highly effective and well-tolerated treatment for ED with SCI. Treatment with PDE-5 inhibitors can significantly improve key quality of life parameters in men with ED caused by SCI (Giuliano et al, 1999(Giuliano et al, , 2006(Giuliano et al, , 2007(Giuliano et al, , 2008Maytom et al, 1999;Hultling et al, 2000;Sánchez Ramos et al, 2001;Kimoto et al, 2006;Lombardi et al, 2009). To our knowledge, we did not come across any study related to the use of vasoactive agents in the early stage after injury including the first 6 months as inclusion criteria.…”
Section: Introductionmentioning
confidence: 75%
“…rigid, or long lasting to enable satisfactory sexual intercourse (Yarkony, 1990;Ducharme et al, 1993). The mean duration of the disease was found to be between 2 and 19.7 years in the literature related to the use of vasoactive agents in patients with SCI (Giuliano et al, 1999(Giuliano et al, , 2006(Giuliano et al, , 2007(Giuliano et al, , 2008Maytom et al, 1999;Hultling et al, 2000;Sánchez Ramos et al, 2001;Kimoto et al, 2006;Lombardi et al, 2009). There was only one study that evaluated the patients with SCI ranging from as early as 6 months to a maximum of 1 year after the injury (Del Popolo et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…In the same study, 59% of the vardenafil group indicated satisfactory duration of erection, compared to 22% of the placebo group. Another open label study, without control, dealing with vardenafil administration in SCL patients, based on 38 patients, indicated achievement of erection, efficient for penetration in 83% of patients and duration of erection satisfactory for 88% of those (Kimoto et al, 2006).…”
Section: Oral Treatmentmentioning
confidence: 99%